The New Conceptual Model for the Net Benefits Improvement in the Intelligent Hanging Production System for Jeans in China - YARUI, HUO (2023)
This thesis explores the factors that influence net benefits in the context of intelligent hanging systems for jeans and examines the relationship between user satisfaction and intention to use. Furthermore, it innovatively constructs a new conceptual model aimed at enhancing the net benefits of intelligent hanging systems for jeans. Employing a mixed research methodology, qualitative research involved interviewing 20 participants, including factory managers and direct users of intelligent hanging systems, while quantitative research analyzed questionnaire responses from 2696 direct users of intelligent hanging systems. Qualitative research identified four core categories through three-level coding, which served as independent variables in quantitative research, mutually reinforcing each other and collectively validating the conceptual model of this study. The results reveal that the factors influencing net benefit production include information quality, system quality, service quality, perceived usefulness (independent variables), and user satisfaction and intention to use (mediating variables). Both user satisfaction and intention to use have a significant and positive influence on net benefits, supporting the ten research hypotheses. Consequently, the newly proposed conceptual model for the net benefits of intelligent hanging systems for jeans receives validation. Qualitative research identified four core categories through three-level coding, which served as independent variables in quantitative research, mutually reinforcing each other and collectively validating the conceptual model of this study. The results reveal that the factors influencing net benefit production include information quality, system quality, service quality, perceived usefulness (independent variables), and user satisfaction and intention to use (mediating variables). Both user satisfaction and intention to use have a significant and positive influence on net benefits, supporting the ten research hypotheses. Consequently, this study validates the newly proposed conceptual model for the net benefits of intelligent hanging systems for jeans. This thesis's theoretical contribution is the innovative construction and validation of a new conceptual model for net benefits, while also extending the DMSM theory in the field of jeans production. Additionally, the practical contribution of this study provides insights for jeans manufacturing enterprises to enhance net benefits, particularly in the adoption or efficient utilization of intelligent hanging systems. The findings will help enterprise managers better allocate resources and implement measures to improve net benefits. Furthermore, the output will assist policymakers in scientifically formulating and implementing intelligent production policies, as well as provide guidance for academia, future research endeavors, and improvement initiatives in the field of intelligent manufacturing.